The Role of Islamic Universities in the Harmony of the Madhhab (Resolution of the Aswaja and Wahabism Conflicts in Aceh) - Juwaini Juwaini; Taslim HM. Yasin; M. Anzaikhan (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
The friction between madhhabs in Aceh, especially between the Ahlisunnah Wal Jamaah (Aswaja) and Wahabi have become increasingly sharp in recent decades. Religious tolerance in Aceh has suffered a setback with the existence of various religious incidents such as the expulsion of preachers, seizure of mosque control, burning of mosque foundations. The Aswaja party is dominated by ulama Dayah (Islamic school scholars) and their followers, while the Wahabi party is aimed at campus Islamic scholars, especially those with Middle Eastern backgrounds. In response to these findings, PTAI (Perguruan Tinggi Agama Islam/Islamic Higher Education) in Aceh offered various solutions. UIN Ar-Raniry seeks to bring together Ulama Dayah and campus scholars to carry out dialogue and consensus. IAIN Langsa prefers not to be involved in the Aswaja and Wahabi conflicts because they consider the friction of madhhab in Aceh is not purely a religious issue, but rather a political one. STAIN Dirundeng Meulaboh is more inclined to the Aswaja and so is the Al-Muslim Bireuen Campus considering having leaders from the Muhammadiyah circle.